Focused ultrasound to transiently disrupt the blood brain barrier. (June 2016) - Mitrasinovic, Stefan; Appelboom, Geoff; Detappe, Alexandre; Sander Connolly, E.
Highlights: First application of MRI-guided Focused Ultrasound to disrupt the BBB on a human patient. The technique is non-invasive, transient and allows BBB disruption to focal regions of interest. Provides potential for a new technique of targeted drug delivery to previously inaccessible brain tissue.